Liberation political science: Power – domination - liberation - Miró Quesada Rada, Francisco (2018)
Liberation Political Science proposes a new method of analysis and new political research objects such as ethics in politics, ideology, liberation and domination. In this article we will explain what domination means and how it is linked to Power. Finally, we will expose the concepts of structural grip and the dominant structural inertia concepts, arguing that domination is the result of structural grip and structural inertia.